The Key Critical Factors Towards Time Delay During The Construction Of Building And Infrastructure Projects In Sarawak - Johnny, Wong Hing Kiong (Universiti Sains Malaysia, 2021)
Nowadays, construction industry has been exposed to lots of risks, especially delay. Construction project delay will lead to time overrun and cost overrun. Project budget will be overspent, extra time are needed to repair the damage due to delay, and finally project failure if this issue is not handled properly. Therefore, this research aims to identify the major factors as well as the key critical delay factors towards time delay during project construction in Malaysia. By acknowledging key critical delay factors, all parties will have high level of preparedness and better measures can be prepared earlier based on those critical factors. The research will be focusing on the building and infrastructure construction projects in Sarawak, Malaysia. 25 delay factors are collected from literature reviews in which they are categorized under owner, contractor, consultant, material, labor, and external factors. Questionnaire is prepared based on those factors and pilot survey is done to check the validity of questionnaire. After pilot survey, questionnaire interviews are conducted with 10 different contractor respondents. The collected data is then analyzed through Analytical Hierarchy Process (AHP) software, Expert Choice 11 to check for the priority importance of delay factors through pairwise comparisons. Finally, a sequential ranking is generated based on the global score for every compared delay factors. From the ranking, the most critical delay factors are low productivity of labors and unskilled workers which are both categorized under labor-related factor. Based on respondents, labor performance is crucial in delivering a construction project on time. These findings are helpful in providing a better guidance for construction communities to propose better mitigations based on the critical delay factors. Project managers can identify the problems earlier, thus minimizing time and cost overruns.